Modelling and simulation of modified skyhook control for semi-active suspension - Ahmad Zaim Solehin, Che Hasan (2011)
The objective of this project is to increase comfort of the vehicle’s passenger. In order to improve comfort and ride quality of a vehicles, there are four parameters need to be acknowledge. The four parameters are sprung mass acceleration,sprung massdisplacement, unsprung displacement and suspension deflection. This project used a new approach in designing the suspension system which is semi-active suspension. The hydraulic damper is replaced by a magneto-rheological damper. A controller is developed for controlling the damping force of the suspension system. The actual concept of the controller is fictitious hence the realization model developed. The controller is called skyhook control. A modified skyhook controller also developed to further improve the suspension system. The semi-active suspension with modified skyhook controller reduces the sprung mass acceleration and displacement hence improving the passengers comfort.